War Experience and Memory in Global Cultures Since 1914
1 online resource (282 pages)
Keywords: "This edited collection explores and develops representations of war experience from 1914 to the ongoing conflicts of the 21st century, through the specific lens of memory. It builds on recent explorations of the importance of war experience in shaping cultural memory that have focused on the aftermath of the First World War and the Second World War, particularly through Holocaust studies. These essays, by a range of international and interdisciplinary scholars, broaden the scope considerably, examining the alternate spaces of the First World War and those that followed it through a range of different media, offering an artistic trajectory to the centennial commemorations of 2014-18."--Provided by publisher.